In Situ Hydroxyapatite Synthesis Enhances Biocompatibility of PVA/HA Hydrogels - Chocholata, Petra; Kulda, Vlastimil; Dvorakova, Jana; Supova, Monika; Zaloudkova, Margit; Babuska, Vaclav (International journal of molecular sciences, 2021)
Bone tissue engineering tries to simulate natural behavior of hard tissues. This study aimed to produce scaffolds based on polyvinyl alcohol (PVA) and hyaluronic acid (HA) with hydroxyapatite (HAp) incorporated in two different ways, by in situ synthesis and physical mixing of pre-prepared HAp. In situ synthesis resulted in calcium deficient form of HAp with lower crystallinity. The proliferation of human osteoblast-like cells MG-63 proved to be better in the scaffolds with in situ synthesized HAp compared to those with physically mixed pre-prepared HAp. For scaffolds with PVA/HA/HAp ratio 3:1:2, there was significantly higher initial adhesion (p = 0.0440), as well as the proliferation in the following days (p < 0.001). It seemed to be advantageous improve the properties of the scaffold by in situ synthesizing of HAp directly in the organic matrix.
Keywords: proliferace buněk; tkáňové podpůrné struktury; biokompatibilní materiály; osteoblasty; hemolýza; buněčná adheze; Polyvinyl Alcohol; lidé; tkáňové inženýrství; bone tissue engineering; polyvinyl alcohol; Hydrogels; Cell Adhesion; kyselina hyaluronová; hydroxyapatite; polyvinylalkohol; Hyaluronic Acid; Durapatite; scaffold; Biocompatible Materials; Materials Testing; cell viability; in situ synthesis; Osteoblasts; hydrogely; Cell Proliferation; testování materiálů; Hemolysis; biological evaluation; Tissue Engineering; hyaluronic acid; hydrogel; Cell Survival; viabilita buněk; Tissue Scaffolds; hydroxyapatit; Humans